Evaluation of pain and vital signs in newborns undergoing physiotherapeutic interventions in a neonatal intensive care unit - Giselda Tavares de Araújo; Igor de Oliveira Loss; Elaine Leonezi Guimarães (BrJP, 2024)
BACKGROUND AND OBJECTIVES: The neonatal intensive care unit (NICU) is a highly complex therapeutic environment for treating high-risk newborns. However, exposure to excessive light, constant manipulation, temperature changes, lack of adequate sleep and invasive procedures can alter vital signs, cause pain and stress, raising concerns about the baby’s neuropsychomotor development. The aim of this study was to analyze the response parameters of newborns admitted to a NICU, checking pain and vital signs during and after physiotherapy intervention. METHODS: This was a cross-sectional observational study with a convenience sample. The participants were assessed before, during and after the physiotherapy intervention, in a single session, observing the variables pain, using the Neonatal Infant Pain Scale (NIPS), and vital signs, using a specific form for collection. RESULTS: Twelve newborns took part in this study, five boys and seven girls, with a mean gestational age of 32.4±3.26 weeks, a mean birth weight of 1677±678.45g and a mean chronological age of 11.5±6.41 days. There was a significant decrease (Z=2.359 and p=0.018) in heart rate after the intervention, and a significant increase (Z=-2.071 and p=0.038) in peripheral oxygen saturation during the intervention. However, the oscillatory parameters remained within the normative values. As for pain, there was no significant difference between the moments before and during (p= 0.41), during and after (p=0.08), and before and after (p=0.18) physiotherapeutic care. CONCLUSION: The results indicated that the physiotherapeutic intervention in the NICU did not cause pain to the newborn.